The Impact of Fertilizer Amendments on Soil Autotrophic Bacteria and Carbon Emissions in Maize Field on the Semiarid Loess Plateau - Wang, Jinbin; Xie, Junhong; Li, Lingling; Luo, Zhuzhu; Zhang, Renzhi; Wang, Linlin; Jiang, Yuji (Frontiers in Microbiology, 2021)
Soil autotrophic bacteria play a crucial role in regulating CO2 fixation and crop productivity. However, the information is limited to how fertilization amendments alter soil autotrophic bacterial community, crop yield, and carbon emission efficiency (CEE). Here, we estimated the impact of the structure and co-occurrence network of soil autotrophic bacterial community on maize yield and CEE. A long-term field experiment was conducted with five fertilization treatments in semi-arid Loess Plateau, including no amendment (NA), chemical fertilizer (CF), chemical fertilizer plus commercial organic fertilizer (SC), commercial organic fertilizer (SM), and maize straw (MS). The results showed that fertilization amendments impacted the structure and network of soil Calvin-Benson-Bassham (CBB) (cbbL) gene carrying bacterial community via changing soil pH and NO3-N. Compared to no amendment, the cbbL-carrying bacterial diversity was increased under the SC, SM, and MS treatments, but decreased under the CF treatment. Soil autotrophic bacterial network contained distinct microbial modules that consisted of closely associated microbial species. We detected that the higher abundances of soil cbbL-carrying bacterial genus were Xanthobacter, Bradyrhizobium, and Nitrosospira. Structural equation modeling further suggested that the diversity, composition, and network of autotrophic bacterial community had strongly positive relationships with CEE and maize yield. Taken together, our results suggest that soil autotrophic bacterial community may drive crop productivity and carbon emission efficiency, mitigate the atmospheric greenhouse effect.